HUBUNGAN PARTISIPASI ORANG TUA DALAM PENDIDIKAN DENGAN PRESTASI AKADEMIK SISWA SEKOLAH DASAR - Rheza Safitri, Yunita Amilia Aini Rohmah, Nur Atikah, Sekar Dwi Ardianti, Erik Aditia Ismaya (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2024)
This research is motivated by the participation of parents in supporting students in academic and non-academic achievements. This research uses a correlational method that looks for the relationship between parental participation in education and student academic achievement. The sample for this research was 13 parents of grade 5 students in one of the elementary schools in Jepara City. The research instrument consists of a questionnaire and documentation. The research results show that there is a relationship between parental involvement in education and elementary school students' learning achievement of 0.003. The figures obtained show that there is a positive relationship between parental participation in education and student academic achievement, the relationship category is at a low level. This means that parental involvement in education has a relationship with student achievement, but there is still a contribution from other factors which have a closer relationship with student achievement, but were not examined in this research.